IMPLIKASI DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DAN DAMPAKNYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN TAKALAR - Rasulong, Ismail (Universitas Muhammadiyah Makassar, 2012)
This study aimed to analyze the effect of equalization funds directly to economic growth and its impact on regional revenue Takalar. The study used secondary data were analyzed using Structural Equation Modelling (SEM). Based on the results of the study concluded that the funds Balance (through tax revenue sharing, profit sharing SDA, General Allocation Fund, Special Allocation Fund and Tax-sharing of province of South Sulawesi) positive effect on the Gross Domestic Product which means that the fund balance is able to enhance economic growth KabupatenTakalar, or it can also mean that the economic growth that occurred in Takalar has been determined by the Fund Balance. Economic growth is positive and significant impact on regional revenue in Takalar, especially directly to local taxes and levies.